2022
DOI: 10.1002/aoc.6695
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies, antimicrobial activity, inhibition of biofilm production, and safety profile of the cadmium complex of 1,10‐phenanthroline and cyanoguanidine

Abstract: We have previously determined the crystal structure of the metal complex [Cd (1,10-phenanthroline) 2 (SO 4 )H 2 O]cyanoguanidine•5H 2 O that was characterized by spectroscopic measurements. The antibacterial activity was also determined by the agar diffusion test (zones of inhibition). In the present work, calculations based on density functional theory were performed to determine the contributions of the two different tautomers of cyanoguanidine to the vibrational IR and Raman experimental spectra. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Across all studies, the inclusion of phen was paramount to the potency of the complexes, with the addition of tddaH 2 enhancing their water solubility and mode of action in various microbial cells, which are problematic in chronic lung diseases, particularly highlighting COPD and lung cancer. A series of complexes incorporating phen and cyanoguanidine (cnge) have been reported with the general formula M(II)/phen/cnge (where M = Cd, Cu, or Zn) [319]. The cadmium complex [Cd(phen) 2 (SO 4 )H 2 O]cnge• 5H 2 O possesses enhanced activity across the assessed bacterial and fungal pathogen in comparison to its metal derivatives.…”
Section: The Activity Of Metal-phen Complexes On Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all studies, the inclusion of phen was paramount to the potency of the complexes, with the addition of tddaH 2 enhancing their water solubility and mode of action in various microbial cells, which are problematic in chronic lung diseases, particularly highlighting COPD and lung cancer. A series of complexes incorporating phen and cyanoguanidine (cnge) have been reported with the general formula M(II)/phen/cnge (where M = Cd, Cu, or Zn) [319]. The cadmium complex [Cd(phen) 2 (SO 4 )H 2 O]cnge• 5H 2 O possesses enhanced activity across the assessed bacterial and fungal pathogen in comparison to its metal derivatives.…”
Section: The Activity Of Metal-phen Complexes On Biofilmsmentioning
confidence: 99%
“…M(II)/phen/cnge (where M = Cd, Cu, or Zn) [319]. The cadmium complex [Cd(phen)2(SO4)H2O]cnge• 5H2O possesses enhanced activity across the assessed bacterial and fungal pathogen in comparison to its metal derivatives.…”
Section: The Activity Of Metal-phen Complexes On Biofilmsmentioning
confidence: 99%
“…O -Phenanthroline monohydrate ( o -Phen) is a metal chelating agent, which can prevent streptozotocin-induced chromosome aberration and is also an inhibitor of matrix metalloproteinases. Studies have reported that o -Phen and its derived compounds exhibit broad-spectrum antibacterial and antifungal activities Candida albicans, interfere with the cell homeostasis of the fungus, and lead to cell death .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some authors have obtained evidence of cell apoptosis as a result of Cd 2+ intoxication; its ability to cause DNA fragmentation is also known [37][38][39]. Cd 2+ ions are considered to be quite toxic, but it has been demonstrated that their toxicity depends on the compound used and therefore can be controlled by complexation [40]. In this context Cd(II)-based coordination compounds with N-containing ligands such as 1,10-phenanthroline may be useful for the development of new antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%